The Pengembangan Desa Tangguh Bencana (DESTANA) sebagai Upaya Peningkatan Ketangguhan Sosial dan Ekonomi Masyarakat Desa Kalibogor - Sari, Mutia Kurnia; Rafidah, Nisrina; Faqih, Muhammad Abdul; Wijayanti, Tutik; Fathon, Zul (FKIP Universitas Wisnuwardhana, 2025)
Indonesia is one of the countries with the highest disaster vulnerability in the world due to its geographical, geological, and tropical climatic conditions. Kalibogor Village, Sukorejo Sub-district, Kendal Regency, is an area with potential natural disasters (landslides, drought) as well as non-natural hazards (traffic accidents and pest attacks). These conditions demand systematic efforts to improve community preparedness and resilience. The purpose of this program is to establish a Disaster Resilient Village (DESTANA) as a platform to strengthen community capacity through a participatory approach. The method used was descriptive qualitative with data collection techniques including participatory observation, semi-structured interviews, and documentation. The activities covered village resilience assessment (PKD), administrative and disaster risk mapping, evacuation route mapping, disaster management planning, establishment of Disaster Risk Reduction Forums (FPRB) and volunteers, as well as training for MSMEs on financial digitalization. The results show an increase in the village resilience score from 126.39 at the beginning to 129.39 at the end of the program, indicating improvements in knowledge, preparedness, and community participation. The program also succeeded in encouraging the formation of institutions and more structured disaster mitigation mechanisms. Thus, DESTANA in Kalibogor Village has provided tangible impacts in strengthening preparedness, fostering self-reliance, and supporting sustainable rural development.